Exercise Training Duration and Intensity Are Associated With Thicker Carotid Intima-Media Thickness but Improved Arterial Elasticity in Active Children and Adolescents - Baumgartner, Lisa; Weberruß, Heidi; Engl, Tobias; Schulz, Thorsten; Oberhoffer-Fritz, Renate (Frontiers in Cardiovascular Medicine, 2021)
Even though exercise generally has a positive effect on health, intensive exercise can have adverse effects on the vascular system of adults. This study aimed to investigate the association between training duration and intensity and vascular structure and function in 427 physically active children and adolescents (14.0 ± 1.95 years). In this study, we examined carotid intima-media thickness (cIMT), carotid diameter, and cIMT:diameter-ratio as parameters of vascular structure and arterial compliance (AC), stiffness index β (β), elastic modulus (Ep), and carotid pulse wave velocity (PWVβ) as parameters of carotid arterial function with high-resolution ultrasound. We collected central systolic blood pressure (cSBP) and aortic pulse wave velocity (aPWV) as parameters of central arterial stiffness with an oscillometric device. We used the MoMo Physical Activity Questionnaire to record the training duration and intensity. Training duration (p = 0.022) and intensity (p = 0.024) were associated with higher cIMT. Further, training duration was associated with lower central arterial stiffness (cSBP: p = 0.001; aPWV: p = 0.033) and improved AC (p < 0.001). Higher training intensity was also related to improved AC (p < 0.001) and larger carotid diameter (p = 0.040). Boys presented thicker cIMT (p = 0.004), improved AC (p = 0.006), and lower central arterial stiffness (cSBP: p = 0.002; aPWV: p = 0.036) associated with higher training duration. Girls presented improved AC (p = 0.023) and lower Ep (p = 0.038) but higher β (p = 0.036) associated with higher training duration. Only boys demonstrated thicker cIMT (p = 0.016) and improved AC (p = 0.002) associated with higher training intensity. The quintile analyses of the training duration revealed thicker cIMT of children and adolescents in Q1 and Q5 than that in Q4 and Q5. Besides, Q1 showed lower cSBP compared to Q4 and Q5. Regarding training intensity, Q5 had thicker cIMT than Q2 and Q3. Although a higher training load is associated with thicker cIMT, the common carotid artery is also more elastic. This suggests that in youth, a higher training load leads to a functional adaptation of the carotid artery.